Hydroxydialkylamino cruciforms: amphoteric materials with unique photophysical properties - McGrier, Psaras; Solntsev, Kyril M.; Zucchero, Anthony J.; Miranda, Oscar R.; Rotello, Vincent M.; Tolbert, Laren M.; Bunz, Uwe H. F. (Chemistry - a European journal, 2011)
Two amphoteric cruciforms 6 and 7 (XF; 4,4′-[(1E,1′E)-(2,5-bis[4-(dibutylamino)phenyl]ethynyl-1,4-phenylene)bis(ethene-2,1-diyl)]diphenol, 4,4′-[2,5-bis[(E)-4-(dibutylamino)styryl]-1,4-phenylenebis(ethyne-2,1-diyl)]diphenol) were prepared by a Horner reaction followed by a Sonogashira coupling and subsequent deprotection. The XFs display significant changes in absorption and emission when exposed to trifluoroacetic acid, tetrabutylammonium hydroxide, and metal triflates. The substitution pattern of 6 and 7 leads to spatial separation of the frontier molecular orbitals, which allows the HOMO or LUMO of the XF to be addressed independently by acidic or basic agents. XF 6, which has hydroxyl groups on the styryl axis, displays changes in emission color upon exposure to ten amines in eight different solvents. The change in fluorescence upon the addition of amines was analyzed by linear discriminant analysis. These XFs may have potential in sensor applications for metal cations and amines.
Gesehen am 15.08.2022